Delivering Aid Differently : Lessons from the Field - Fengler, Wolfgang; Kharas, Homi (World Bank, Washington, DC, 2012)
Delivering aid differently was written at a time when the future of foreign aid is being fiercely debated. The book includes an overview; case studies of Aceh/Indonesia, Cambodia, Ethiopia, Kenya, Pakistan, and Tajikistan; and thematic chapters on joint assistance strategies, information systems, and humanitarian aid. This new aid environment is characterized by three important shifts that have emerged in the last decade: 1) strong growth in many developing countries has redefined the role of aid; 2) the donor landscape has changed fundamentally over the last decade, a trend that will likely accelerate in the coming years; and 3) innovation, especially in information technology, has started to reshape development aid. Knowledge transfer has become as important as financial aid, and combining the two can be remarkably transformative. The author advocates two institutional changes. First, authors encourage the development of one (or more) geographically based development authorities within poor countries, with a focus on providing the information that is needed to run an efficient aid program. Second, authors argue for an international body of national development aid agencies to deliberate, share best practices, and provide an informal mechanism for holding aid agencies accountable to their ultimate beneficiaries-the poor people of the world.